2013
DOI: 10.1093/bja/aet231
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic drugs and survival: a Bayesian network meta-analysis of randomized trials in cardiac surgery

Abstract: Anaesthesia with volatile agents appears to reduce mortality after cardiac surgery when compared with TIVA, especially when sevoflurane or desflurane is used. A large, multicentre trial is warranted to confirm that long-term survival is significantly affected by the choice of anaesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
117
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 39 publications
2
117
2
7
Order By: Relevance
“…9 When compared with intravenous anesthesia, sevoflurane has been shown to reduce the incidence of MI and intensive care unit stay, the length of time on mechanical ventilation following cardiac surgery, in-hospital mortality, and long-term cardiac events. [10][11][12][13][14] The effect of sevoflurane as a cardioprotective agent has not been shown in all studies, 15 and results were also dependent on duration of administration, number of exposures, and dose. For instance, in one study, the beneficial effects were observed only when administered throughout the surgery and not when administered in a fashion similar to ischemic conditioning, before cardiopulmonary bypass, or following the creation of the coronary anastomosis.…”
Section: Résumémentioning
confidence: 92%
“…9 When compared with intravenous anesthesia, sevoflurane has been shown to reduce the incidence of MI and intensive care unit stay, the length of time on mechanical ventilation following cardiac surgery, in-hospital mortality, and long-term cardiac events. [10][11][12][13][14] The effect of sevoflurane as a cardioprotective agent has not been shown in all studies, 15 and results were also dependent on duration of administration, number of exposures, and dose. For instance, in one study, the beneficial effects were observed only when administered throughout the surgery and not when administered in a fashion similar to ischemic conditioning, before cardiopulmonary bypass, or following the creation of the coronary anastomosis.…”
Section: Résumémentioning
confidence: 92%
“…A meta-analysis published in 2013, combining standard and Bayesian approaches on studies performed in adult cardiac surgery patients, concluded that inhaled anaesthesia, as opposed to total intravenous anaesthesia, was associated with a 50% decrease in mortality (from 2.6% in the total intravenous anaesthesia arm to 1.3% in the inhaled anaesthetics arm); the Bayesian meta-analysis concluded that mortality was the lowest when sevoflurane was used as the anaesthetic agent. 247 Comparable data relating to non-cardiac surgery are scarce. One small study observed a lower incidence of major cardiac events in vascular surgery patients anaesthetized with a volatile agent than with an intravenous anaesthetic, 248 but two other studies in non-cardiac surgery patients observed no difference in outcome.…”
Section: Anaesthesiamentioning
confidence: 99%
“…[3][4][5] In the current issue of the Journal, Ansley et al have pursued a different approach: They report the results of their clinical Phase 2 trial (PRO-TECT II) that assessed the impact of administering a targeted dose of systemic propofol during the ischemia-reperfusion interval in patients undergoing heart surgery. 6 They hypothesized that the antioxidant properties of propofol impart anesthetic preconditioning and protect ischemic myocardium from oxidative injury during cardiac surgery.…”
mentioning
confidence: 99%
“…In juxtaposition to Ansley et al, several meta-analyses have demonstrated trends toward more favorable outcomes with inhalation anesthetics. [3][4][5] Yu and Beattie assessed a heterogeneous group of studies that demonstrated a trend toward decreased mortality with inhalation anesthetics. 3 Sevoflurane and desflurane, but not isoflurane, were associated with a decrease in postoperative troponin levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation